Cerebral Blood Flow Reduction Associated with Orientation for Time in Amnesic Mild Cognitive Impairment and Alzheimer Disease Patients. Issue 6 (5th March 2014) - Yamashita, Ken‐ichiro; Taniwaki, Yoshihide; Utsunomiya, Hidetsuna; Taniwaki, Takayuki
ABSTRACT: BACKGROUND AND PURPOSE: Impairment of orientation for time (OT) is a characteristic symptom of Alzheimer disease (AD). However, the brain regions underlying OT remain to be elucidated. Using single photon emission computed tomography (SPECT), we examined the brain regions exhibiting hypoperfusion that were associated with OT. METHODS: We compared regional cerebral blood flow (rCBF) differences between AD and amnesic mild cognitive impairment (aMCI) or normal subjects using 3‐dimensional stereotactic surface projection (3D‐SSP) analysis. AD patients were divided into OT good and poor groups according to their mean OT scores, and rCBF then compared between the groups to elucidate OT‐specific brain areas. RESULTS: 3D‐SSP analysis showed reduced rCBF in the left superior parietal lobule (SPL) and bilateral inferior parietal lobule (IPL) in AD patients. In the poor OT group, 3D‐SSP analysis revealed hypoperfusion in the bilateral SPL, IPL, posterior cingulated cortex (PCC), and precuneus. Among these areas, region of interest analysis revealed a significant higher number of hypoperfused pixels in the left PCC in the OT poor AD group. CONCLUSIONS: Our SPECT study suggested that hypoperfusion in the left SPL and bilateral IPL was AD specific, and reduced rCBF in the left PCC was specifically associated with OT.